2001
DOI: 10.1084/jem.193.12.1341
|View full text |Cite
|
Sign up to set email alerts
|

Control of Von Willebrand Factor Multimer Size by Thrombospondin-1

Abstract: Plasma von Willebrand factor (vWF) is a multimeric protein that mediates adhesion of platelets to sites of vascular injury. Only the very large vWF multimers are effective in promoting platelet adhesion in flowing blood. A protein disulfide bond reductase in plasma reduces the average multimer size of vWF secreted by endothelial cells. This activity has been isolated from human endothelial cell conditioned medium and shown to be the trimeric glycoprotein, thrombospondin-1 (TSP-1). Incubation of purified TSP-1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
105
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(105 citation statements)
references
References 40 publications
0
105
0
Order By: Relevance
“…In the extracellular space, the Ser-700 polymorphism may alter interactions of the C-terminal region of TSP-1 with hemostatic proteins such as thrombin (31) and von Willebrand factor (32,33), which bind covalently to TSP-1 via disulfide bonding at the C terminus. Recently, the presence of the Ser-700 polymorphism in TSP-1 has been shown to increase binding of TSP-1 to fibrinogen on the platelet surface, resulting in increased platelet aggregation (30).…”
Section: The Tr1 Constructs Contain An Intact Tb 3ϩ -Binding Site-mentioning
confidence: 99%
“…In the extracellular space, the Ser-700 polymorphism may alter interactions of the C-terminal region of TSP-1 with hemostatic proteins such as thrombin (31) and von Willebrand factor (32,33), which bind covalently to TSP-1 via disulfide bonding at the C terminus. Recently, the presence of the Ser-700 polymorphism in TSP-1 has been shown to increase binding of TSP-1 to fibrinogen on the platelet surface, resulting in increased platelet aggregation (30).…”
Section: The Tr1 Constructs Contain An Intact Tb 3ϩ -Binding Site-mentioning
confidence: 99%
“…22 Equal concentrations (0.5 g/mL) of wild type (wt) or mutant VWF or normal pooled plasma diluted in PBS were incubated with 100 M malemide-PEO 2 -Biotin (MPB; Thermo) for 10 minutes at room temperature and the reaction quenched with 200 M GSH. Samples were then diluted with PBS-T to final concentration 0.25 g/mL and applied to MaxiSorp plates that had been previously coated with polyclonal anti-VWF antibodies and incubated for 1 hour at room temperature.…”
Section: Analysis Of Free Thiol Content Of Vwfmentioning
confidence: 99%
“…But at least a subset of these antibodies also shows features of autoreactivity. 2 Parallels between these 2 syndromes are well recognized, 3 but the final link between them has remained enigmatic. In this issue of Blood, Sikara et al demonstrate in a series of in vitro experiments an interaction between ␤2-GPI and PF4.…”
Section: Opposites Attract ------------------------------------------mentioning
confidence: 99%
“…Consistent with the notion, an early report has shown that thiol(s) in the VWF A3 domain is targeted by a reductase activity associated with thrombospondin-1. 3 The question remains as to whether different reactive oxygen species differentially modify specific amino acids within a VWF multimer, leading to different functional outcomes. Second, does oxidation also affect VWF adhesion activity?…”
Section: Jing-fei Dong Baylor College Of Medicinementioning
confidence: 99%